A Meta-Analysis on the Significance of Dietary Omega-3 Fatty Acids on Bone Development and Quality in Egg- and Meat-Type Chickens - Thanabalan, Aizwarya; Ellis, Jennifer; Kiarie, Elijah G. (Frontiers in Animal Science, 2022)
Poultry egg and meat production continue to be optimized for productivity and efficiency. However, genetic selection focusing on production efficiency has overlooked other aspects critical to bird wellbeing, such as skeletal development. As a result, modern birds are more prone to leg weakness, osteoporosis, and, subsequently, fractures. Dietary omega-3 polyunsaturated fatty acid (n-3 PUFA) enrichment has been proposed to benefit bone development, quality, and strength. However, there is a lack of conclusive and quantitative results across studies. Therefore, a meta-analysis approach was used to evaluate published studies to determine the effects of dietary n-3 PUFA enrichment on bone quality in laying- and meat-type birds. Publications were retrieved from multiple sources (databases and hand searching), and ten studies were selected for inclusion in the final dataset. A model to predict tibial bone ash content (BAC) was developed in Proc MIXED of SAS, treating the study as a random effect. The dietary concentration of n-3 PUFA, n-3 PUFA:n-6 PUFA ratio, calcium (Ca), phosphorus and feeding duration (days) were used as independent variables to predict BAC. The final model included the dietary n-6:n-3 FA ratio and the calcium concentration in the diet. The final model was selected based on the corrected Akaike Information Criteria, the root mean square prediction error (0.999) and its components, and the concordance correlation coefficient (CCC) (0.99). In laying-type birds, BAC was reduced by n-3 PUFA (p = 0.001) but was increased by Ca (p = 0.014). In contrast, in broiler chickens, BAC was increased by n-3 PUFA (p = 0.001) and decreased by Ca (p = 0.014). The influence of n-3 PUFA:n-6 PUFA ratio on tibia BAC in laying-type birds was not statistically significant (p = 0.505), whereas in meat-type birds, the influence of PUFA ratio was significant (p < 0.05). These results may indicate a low biological significance in laying-type birds but not in meat-type birds.